Analysis of Plasma Electrolytic Oxidation Process Parameters for Optimizing Adhesion in Aluminum–Composite Hybrid Structures - Lucas, Rafael Resende [UNESP]; Silva, Emanuelle Roza Rodrigues [UNESP]; Marques, Luís Felipe Barbosa [UNESP]; da Silva, Francisco José Gomes; Abrahão, Ana Beatriz Ramos Moreira; Vieira, Miguel de Omena Lucas [UNESP]; Hein, Luís Rogério de Oliveira [UNESP]; Botelho, Edson Cocchieri [UNESP]; Mota, Rogério Pinto [UNESP]; Sales-Contini, Rita de Cássia Mendonça (MDPI, 2024)
The Plasma Electrolytic Oxidation (PEO) process was investigated to enhance the adhesion of AA2024-O aluminum alloy with a polyetherimide (PEI) matrix composite, using oxy-fuel welding (OFW). A Central Composite Design (CCD) statistical model was used to optimize three independent parameters in PEO: immersion time (s), duty cycle (%), and electrolyte concentration (Na2B4O7·10H2O), aiming to achieve a maximum value of shear strength of the hybrid joint (in MPa). The hybrid joint without PEO treatment presented a resistance of 2.2 MPa while the best condition presented a resistance of 9.5 MPa, resulting in a value 4× higher than the untreated material, due to the characteristics of the coating, which presented a more hydrophilic surface, allowing better mechanical interlocking with the polymer matrix and resulting in mixed-mode failure (adhesive, cohesive, and light fiber). In addition to improving adhesion, the PEO treatment provided better corrosion resistance to the alloy, forming an inert aluminum oxide (Al2O3) coating, with an improvement of approximately 99.84% compared to the untreated alloy. The statistical design covers about 77.15% of the total variability of the PEO + welding process, with independent factors influencing around 48.4% of the variability.
Keywords: aluminum; characterizations; composite; plasma treatment; welding